Emancipating Calvin : culture and confessional identity in Francophone Reformed communities : essays in honor of Raymond A. Mentzer, Jr. - Mentzer, Raymond A.; Spierling, Karen E., 1970-; Boer, Erik Alexander de.; Holder, R. Ward. (Brill's Series in Church History, 2018)
The eleven essays in Emancipating Calvin: Culture and Confessional Identity in Francophone Reformed Communities demonstrate the vitality and variety of early modern Francophone Reformed communities by examining the ways that local contexts shaped the reception and implementation of reforming ideas emanating especially from John Calvin and the Reformed church of Geneva. The articles address three main themes important for understanding the development of Reformed communities: the roles of consistories in Reformed churches and communities, the development of various Reformed cultures, and the ways in which ritual and worship embodied the theology and cultural foundations of Francophone Reformed churches. This Festschrift honors the pioneering work of Raymond Mentzer and reflects his influence in modern Francophone Reformed studies.